Protein crystallography beamline BL2S1 at the Aichi synchrotron. (19th December 2016) - Watanabe, Nobuhisa; Nagae, Takayuki; Yamada, Yusuke; Tomita, Ayana; Matsugaki, Naohiro; Tabuchi, Masao
Abstract : The protein crystallography beamline BL2S1 has been constructed on the 5 T superbend port of the AichiSR. Abstract : The protein crystallography beamline BL2S1, constructed at one of the 5 T superconducting bending‐magnet ports of the Aichi synchrotron, is available to users associated with academic and industrial organizations. The beamline is mainly intended for use in X‐ray diffraction measurements of single‐crystals of macromolecules such as proteins and nucleic acids. Diffraction measurements for crystals of other materials are also possible, such as inorganic and organic compounds. BL2S1 covers the energy range 7–17 keV (1.8–0.7 Å) with an asymmetric‐cut curved single‐crystal monochromator [Ge(111) or Ge(220)], and a platinum‐coated Si mirror is used for vertical focusing and as a higher‐order cutoff filter. The beamline is equipped with a single‐axis goniometer, a CCD detector, and an open‐flow cryogenic sample cooler. High‐pressure protein crystallography with a diamond anvil cell can also be performed using this beamline.